Makna Pertobatan Lahir dan Batin Menurut St. Yohanes XXIII dalam Ensiklik Paenitentiam Agere - Megawati Naibaho; Blasius Superma Yese; Ardiana Waruwu (Jurnal Magistra, 2024)
Human being having a conscience and freedom to determine what is good and performing actions according to God's will. In today's era, phenomena show that human being sometimes ignores the Divine law and do not listen to their conscience. These acts of infidelity drive a human being to fall into sin and live contradict according to God's will. However, God through the Holy Church always gives the human being the opportunity to revert to God. The Church provides the special opportunity to repent, explicitly through the Sacrament of Reconciliation . It was emphasized by St. John XXIII in the Encyclical Paenitentiam Agere. The method used is a literature study, especially studying the Encyclical Paenitentiam Agere. The results of the study show that the spirit of repentance as proclaimed in the Encyclical Paenitentiam Agere says that only through repentance the Christians will nurture in the perfection of life. The repentance according to St. John XXIII is a repentance of the body and soul. The conclusion of this study confirms that inner repentance is a repentance carried out by Christians through a good confession of sins and taking part in the Eucharistic sacrifice and receiving holy communion. Inner repentance is realized in everyday life through daily actions called external repentance. By doing external and internal repentance, the Christians will obtain true happiness and salvation from God.